Environmental parameters of a coral assemblage from the Akerchi Formation (Carboniferous), Adarouch Area, central Morocco - Said, I.; Rodríguez, S.; Berkhli, M.; Cózar, P.; Gómez-Herguedas, A. (Journal of Iberian Geology, 2010)
Rich assemblages of rugose corals occur in the Tizra, Akerchi and Idmarrach formations (Mississippian) near El-Hajeb City. The Akerchi Formation, approximately 140 m thick, is divided into two members. The upper part of the lower member contains a biostrome 2 to 5 m thick, composed mainly of rugose corals and gigantoproductid brachiopods embedded in marly limestone. Its local thickness increases from southwest to northeast in an outcrop extending for more than one kilometre. The Akerchi biostrome is mostly composed of rugose corals. Brachiopods, bryozoans, porifera (chaetetids, sponges), and molluscs are conspicuous elements of the biostrome, but none of them constitutes a significant component. Other common fossil taxa in thin sections are foraminifers, algae and cyanobacteria, ostracods, trilobites and echinoderms. The coral assemblage in the biostrome is regarded as a paleocommunity, because the biostrome is not composed of distinct coral bearing beds in different time slices, but rather, it is a mass of corals which in many instances show their original relationships and continuous colonial growth. The assemblage is diverse, including 12 genera and 20 species. Micro- and macrofacies analyses of corals and surrounding rock allowed some environmental inferences: a high level of energy is suggested by the degree of fragmentation of branches in fasciculate colonies and other features of the rocks. However, the energy was not high enough to destroy the colonies, and the presence of abundant micrite indicates that the energy level was discontinuous. Other environmental factors inferred from paleoecological and taphonomical evidences are shallow water with normal marine salinity and a hard substrate provided by quick cementation of oolite bar and by abundant bioclasts. Massive coral colonies and gigantoproductids are attached directly to the oolite bar which in turn provided a hard susbstrate for attachment of fasciculate corals that are dominant in the biostrome.